Is anything left of the debate about the sources of growth in East Asia thirty years later? - Jesus Felipe; John S. L. McCombie (Levy Economics Institute of Bard College, 2023)
The year 2023 commemorates the 30th anniversary of the publication of the influential, yet controversial, study The East Asian Miracle report by the World Bank (1993). An important part of the report's analysis was concerned with the sources of growth in East Asia. This was based on the neoclassical decomposition of growth into productivity and factor accumulation. At about the same time, the publication of Alwyn Young's (1992, 1995) and J. I. Kim and Lawrence Lau's (1994) studies, and Paul Krugman's (1994) popularization of the "zero total factor productivity growth" thesis, led to a very important debate within the profession, on the sources of growth in East Asia. The emerging literature on China's growth during the 1990s also used the neoclassical growth model to decompose overall growth into total factor productivity growth and factor accumulation. This survey reviews what the profession has learned during the last 30 years about East Asia's growth, using growth-accounting exercises and estimations of production functions. It demystifies this literature by pointing out the significant methodological problems inherent in the neoclassical growth-accounting approach. We conclude that the analysis of growth within the framework of the neoclassical model should be seriously questioned. Instead, we propose that researchers look at other approaches, for example, the balance-of-payments-constrained growth rate approach of Thirlwall (1979) or the product space of Hidalgo et al. (2007), together with the notion of complexity of Hidalgo and Hausmann (2009).
Keywords: O10; O47; O53; 330; Accounting Identity; Biased Technological Progress; China; East Asia; Growth Accounting; Dual TFP; Primal TFP